1998
DOI: 10.1038/bjc.1998.444
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the TP53 gene and protein expression of p53, MDM 2 and p21/WAF-1 in primary cervical carcinomas with no or low human papillomavirus load

Abstract: Several studies have focused on the role of p53 inactivation in cervical cancer, either by inactivating mutations in the TP53 gene or by degradation of the p53 protein by human papillomavirus (HPV). In this study, primary cervical carcinomas from 365 patients were analysed for presence of HPV using both consensus primer-sets and type-specific primer-sets. Nineteen samples were determined to have no or low virus load, and were selected for further analyses: mutation screening of the TP53 gene using constant den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 23 publications
(10 reference statements)
2
15
0
Order By: Relevance
“…The p53 Arg72Pro polymorphisms were analysed by procedures modified from those described by Helland et al [35] and Ara et al [36]. A 199-bp sequence containing the polymorphic site was amplified by PCR using the following primers:…”
Section: Analysis Of Tp53 Codon 72 Polymorphismmentioning
confidence: 99%
“…The p53 Arg72Pro polymorphisms were analysed by procedures modified from those described by Helland et al [35] and Ara et al [36]. A 199-bp sequence containing the polymorphic site was amplified by PCR using the following primers:…”
Section: Analysis Of Tp53 Codon 72 Polymorphismmentioning
confidence: 99%
“…Using immunohistochemical techniques, overexpression of MDM2 protein (with or without gene amplification) has been reported in various human cancers, including breast cancer [75,96,[114][115][116][117], ovarian cancer [118,119], cervical carcinoma [120][121], endometrial carcinoma [122], choriocarcinoma [123], soft tissue sarcomas, osteosarcomas, rhabdomyosarcomas, leiomyomas, and leiomyosarcomas [88,[124][125][126][127][128][129][130][131][132][133][134][135][136][137][138][139], head and neck cancers [106,[140][141][142][143][144][145][146][147][148][149][150], lung and bronchogenic carcinomas [103][104][105][151][152]…”
Section: The Mdm2 Oncogene and Cancermentioning
confidence: 99%
“…Cervical cancer development is the result of complex interactions between the host and environmental factors, undergoing stepwise progression from low-grade to high-grade dysplasia to invasive carcinoma. In this pathway, activation or inactivation of various cancer-related genes is involved [3,17,31,39]. Recent studies have demonstrated the promoter hypermethylation of several genes, such as DAPK, p16 INK4A , O6-methylguanine-DNA methyltransferase (MGMT), APC, HIC-1, E-cadherin, RARß, FHIT, GSTP and hMLH1, associated with cervical carcinogenesis [13,24,43,45,48].…”
Section: Introductionmentioning
confidence: 99%